2023
DOI: 10.1088/1475-7516/2023/09/028
|View full text |Cite
|
Sign up to set email alerts
|

Sweeping Horndeski canvas: new growth-rate parameterization for modified-gravity theories

Yuewei Wen,
Nhat-Minh Nguyen,
Dragan Huterer

Abstract: We propose and numerically validate a new fitting formula that is sufficiently accurate to model the growth of structure in Horndeski theories of modified gravity for upcoming Stage IV and V large-scale structure surveys. Based on an analysis of more than 18,000 Horndeski models and adopting the popular parameterization of the growth rate f(z) = Ω M (z) γ , we generalize the constant growth index γ to a two-parameter redshift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Despite the model being purely phenomenological, a measurement of γ inconsistent with its ΛCDM prediction would provide a clear detection of deviations from the standard cosmological model. On the other hand, it has been shown that the growth index parameterisation can provide a good fit for specific modified gravity models, such as the DGP model [37], with γ ≃ 0.67 [38,39], and a class of Horndeski theories [40], although in that case a time dependent growth index is required. For this reason a precise measurement of the growth index is among the objectives of forthcoming Stage-IV surveys [10,14,41].…”
Section: Jcap12(2023)025mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the model being purely phenomenological, a measurement of γ inconsistent with its ΛCDM prediction would provide a clear detection of deviations from the standard cosmological model. On the other hand, it has been shown that the growth index parameterisation can provide a good fit for specific modified gravity models, such as the DGP model [37], with γ ≃ 0.67 [38,39], and a class of Horndeski theories [40], although in that case a time dependent growth index is required. For this reason a precise measurement of the growth index is among the objectives of forthcoming Stage-IV surveys [10,14,41].…”
Section: Jcap12(2023)025mentioning
confidence: 99%
“…(2.10) and (2.11) are then used to re-scale the linear power spectrum computed at redshift z = 0 and construct the redshift space multipoles as described in section 2.1. An analysis of the behaviour of γ over cosmic history can be found in [67,68], while [40] propose an alternative parameterisation, that extends γ to be a function of redshift.…”
Section: Jcap12(2023)025mentioning
confidence: 99%
“…Therefore, one can probe the CDM model by measuring the growth index γ , because it has potential to distinguish GR and modified gravity models [21,[25][26][27][28]. In fact, a possible evidence for the growth index evolution and its cosmological implications has been recently discussed [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%